PENGARUH MOTIVASI TERHADAP HASIL BELAJAR DAN KARAKTER TANGGUNG JAWAB SISWA DALAM MUATAN PKN - Abdul Malik Ibrahim; Laelia Nurpratiwiningsih; Diah Sunarsih (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Purwokerto, 2020)
Abstract. Education is one effort that is conscious of the goal with systematically directed at changing behavior towards maturity of students. The method used in this research is quantitative correlation. Data collection techniques using questionnaires, tests and documentation. This quantitative research instrument uses a questionnaire and multiple choice tests. The results obtained are (1) there is an influence of motivation with learning outcomes obtained a significant value of probability of 0.026, which means less than 0.05, (2) there is an influence of motivation towards responsibility from the t test results obtained a significant value of probability of (0,000<0.05), (3) motivation towards learning outcomes and responsibility from the F test results obtained a significance score of 0,000, so it is concluded motivation is a change in energy in a person characterized by the emergence of “feeling” and preceded by a response to the existence of goals.